DIPLOMATIC RELATIONS BETWEEN ACEH AND TURKEY DURING THE REIGN OF SULTAN ALAUDDIN MANSUR SHAH (1577-1585 / 1586) - Khairul Nizam Bin Zainal Badri (JURNAL PENELITIAN SEJARAH DAN BUDAYA, 2021)
Aceh is regarded as the strongest ally of the Ottomans in the east, in the 16th century and 17th century AD. At that time, the two governments exchanged gifts with each other, and benefited together; whether in the form of trade, or in the form of technology and the military. The historical record notes that Aceh started making official relations with the Ottomans during the reign of Sultan Salahuddin, which is the 2nd in the Sultanate of Aceh. Yet to be studied in this paper is that the establishment of diplomatic relations between Aceh and Turkey during the reign of Sultan Alauddin Mansur Shah. Remarkably, Sultan Alauddin Mansur Shah hailed from Perak, but was crowned the 8th Ruler of Aceh. This qualitative study uses the library approach entirely to highlight the role and contribution of Sultan Alauddin Mansur Shah in efforts to strengthen cooperation between Aceh and Turkey. With the help of the Ottomans, he launched an attack on the Portuguese in Melaka. Aceh’s strength even feared by the Portuguese authorities in Goa, India, forcing them to seek assistance from Lisbon. In conclusion, Sultan Alaudin Mansur Shah not only gained recognition from the Ottoman government but also succeeded in upholding the greatness of Islam; when reviving the trade routes of Muslims and looking after the welfare of Muslims in the archipelago.